Bioimpedance Body Measures and Serum Lipid Levels in Masculine Depression - von Zimmermann, Claudia; Brückner, Lena; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder is a main reason for suicide, and serum lipids are involved in both affective disorders and related suicidal behavior. Moreover, masculine depression has been suggested as a subtype of depression with increased risk for suicide. Here, we studied the relationship between body measures, serum lipids, suicidal thoughts, and masculine depression. Methods: Depressed patients (44% women) were divided by a sex-separated median-split into a group of 81 “patients with masculine depression” (mean age ± standard error: 36.4 ± 1.6 years) and a group of 82 “patients with non-masculine depression” (age 45.7 ± 1.6 years) according to the Male Depression Risk Scale. We compared body measures, serum lipid levels, and past suicidal ideation between these groups and explored differences to 176 healthy controls (51% women; age 37.2 ± 1.0 years). Results: Patients with masculine depression did not significantly differ from patients with non-masculine depression in any of the body measures, lipid markers, or suicidal thoughts. Compared to healthy controls, both patient groups showed significantly higher body fat (B[masculine and non-masculine] = 0.041 and 0.050), lower HDL cholesterol (B = -0.045 and -0.044), and a higher risk for suicidal thoughts (B = 3.927 and 2.663) than healthy controls. Suicidal thoughts were significantly associated with lower LDL/HDL ratios (B = -0.455) in patients with depression and with higher LDL cholesterol levels (B = 0.020) in healthy controls subjects. Limitations: Correlational study design and focus on in-patients. Conclusions: In the studied cohort, masculine depression was not significantly associated with the analyzed parameters of body measures, serum lipids, or suicidal thoughts in in-patients with depression.